The Scopus Radar Readiness Model for Mitigating Algorithmic Discontinuation Risks - Eko Pramudya Laksana; Ikhwan Arief; Mochammad Tanzil Multazam; Busro Busro; Arif Zainudin; Akhmad Anwar Dani; Andista Candra Yusro; Dedi Rahman Nur; Utama Alan Deta; Much Fuad Saifuddin; Mohammad Fauziddin; Muhamad Ratodi; Asep Erlan Maulana; Muh. Firyal Akbar; Lucky Zamzami; Aldy Rialdy Atmadja; Eko Pramudya Laksana; Ikhwan Arief; Mochammad Tanzil Multazam; Busro Busro; Arif Zainudin; Akhmad Anwar Dani; Andista Candra Yusro; Dedi Rahman Nur; Utama Alan Deta; Much Fuad Saifuddin; Mohammad Fauziddin; Muhamad Ratodi; Asep Erlan Maulana; Muh. Firyal Akbar; Lucky Zamzami; Aldy Rialdy Atmadja (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The integrity of the global academic record is under unprecedented threat due to the industrialization of scientific misconduct, driven by paper mills, citation cartels, and identity theft, prompting major bibliographic databases to replace manual curation with algorithmic systems. This study examines the operational mechanics of the Scopus Radar tool, an unsupervised anomaly detection system designed to identify and eliminate articles exhibiting anomalous behavior. We reconstruct the bibliometric indicators that lead to discontinuation by triangulating data from the November 2025 Scopus Discontinued Titles list, public Elsevier policy papers, and independent bibliometric research. Our study of 62 cancelled journals shows that Publication Concerns (59.7%) and Outlier conduct (14.5%) are the top grounds for removal. There are definite tendencies when it comes to hyper-concentrated authorship, quick volume velocity spikes, and citation stacking that does not make sense. We also see a "contagion effect," where certain publications have far greater rates of quitting than others. Based on these findings, we propose the Scopus Radar Readiness Model (SRRM). The model is based on the Core Practices of the Committee on Publication Ethics (COPE) and has four stages of growth. This roadmap gives editorial boards the tools they need to go from reactive compliance to proactive integrity assurance. They can do this by using internal bibliometric audits to find and fix problems before they lead to external algorithmic enforcement. The results show that journals need to use Level 4 Optimized integrity practices to stay alive in a time when automated gatekeeping is common.